Theoretical analysis of adsorption of various compounds onto hydrophilic and hydrophobic silicas compared to activated carbons - V. M. Gun'ko (Хімія, фізика та технологія поверхні, 2019)
The aim of this study was to analyze various theoretical models (clusters, systems with periodic boundary conditions) and methods, which could be applied to investigate the adsorption phenomena and for better interpretation of the experimental data. The density functional theory (DFT) and semiempirical (PM7) methods were used to model the adsorption phenomena at a surface of fumed nanooxides, silica gels, activated carbons, etc. The main idea is that appropriate theoretical analysis allows a deeper insight into interfacial phenomena related to the structure & properties of the adsorption layers vs. the textural and other characteristics of adsorbents. Comparison of the theoretically calculated characteristics with experimental ones can allow more accurate interpretation of the effects observed in various experiments on the adsorption phenomena. It was established that polarization of nonpolar and polar molecules adsorbed onto a polar surface and charge (& proton) transfer play an important role, as well as confined space effects. It enhances the interaction energy of adsorbed molecules bound to a solid surface and affects the surface orientation of adsorbed molecules, as well the behavior of the adsorption layer vs. temperature, pressure or concentration, as well other conditions. Surface hydrophobization reduces the interaction energy for both polar and nonpolar adsorbates. Adsorbates clusterization reduces the average energy of interaction of the adsorption layer with a surface per a molecule. The charge transfer is observed for both polar and nonpolar molecules interacting with polar surface functionalities. The mostly strong interfacial effects changing the behavior of the adsorption layer are observed upon proton transfer to the adsorbed molecules or vice versa. Variation in orientation of adsorbed molecules results in overestimation of the specific surface area estimated using a fixed value of surface area occupied by a probe molecule (e.g. 0.162 nm2 for N2).